From Mustahik to Muzaki: Analyzing Career Outcomes and Poverty Alleviation through the Beasiswa Cendekia BAZNAS Program - Triono, M. Haris Surya; Septian, Farid; Umam, Ahmad Khotibul (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
The Beasiswa Cendekia BAZNAS Program is designed to support students in completing their undergraduate education while promoting poverty alleviation by transforming mustahik (beneficiaries) into muzaki (donors). This research analyzes the program’s effectiveness using a mixed-method approach, incorporating qualitative interviews with BAZNAS RI stakeholders and quantitative analysis of alumni tracer data to examine academic factors influencing alumni career outcomes. The findings reveal that academic factors significantly impact alumni career achievements. For instance, the 2018 alumni cohort has higher incomes compared to other cohorts, influenced by longer work experience and additional scholarship stipends during their studies. Furthermore, alumni from public universities and those in STEM fields tend to have the highest income levels, underscoring the significance of institutional reputation in the job market. Compared to the National Poverty Line 2024, 100% of the alumni are above this threshold. However, when compared to the Had Kifayah per capita per month, 18% of alumni are still below or near it, 70% have exceeded it but have not yet reached the zakat threshold, and 12% have reached the zakat threshold. This reflects the program's success in achieving its goals of poverty alleviation (moving out of poverty) and transforming mustahik into muzaki (moving out of mustahik). This research contributes academically by enriching the literature on the impact of philanthropic scholarships on the economic independence of its recipients. Practically, these findings can help BAZNAS enhance the effectiveness of its scholarship program by emphasizing factors that boost alumni career readiness and competitiveness.